Urban violence and public health in Latin America: a sociological explanatory framework Violencia urbana y salud pública en Latinoamérica: un marco sociológico explicativo - Roberto Briceño-León (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
Interpersonal violence has become one of the main public health issues in Latin American cities. This article presents a framework for sociological interpretation that operates on three levels, expressed in the factors that originate, foment, or facilitate violence. Macro-social factors include: social inequality due to the increase in wealth versus poverty; the paradox of more schooling with fewer employment opportunities; increasing expectations and the impossibility of meeting them; changes in family structure; and loss of importance of religion in daily life. At the meso-social level the analysis highlights: increased density in poor areas and urban segregation; masculinity cult; and changes in the local drug market. The micro-social level includes: an increase in the number of firearms; alcohol consumption; and difficulties in verbal expression of feelings. The article concludes with an analysis of how violence is leading to the breakdown not only of urban life but also of citizenship as a whole in Latin America. La violencia interpersonal se ha convertido en uno de los principales problemas de salud pública de las ciudades de América Latina. El artículo presenta una interpretación sociológica de la violencia en tres niveles: (a) macro-sociales la desigualdad social debida al incremento de la riqueza y la pobreza; la paradoja del mayor nivel educativo de las personas, pero las menores oportunidades de empleo, el incremento de las expectativas y de la imposibilidad de satisfacerlas; los cambios en la familia y la pérdida de importancia de la religión en la vida cotidiana de las personas; (b) meso-sociales el incremento de la densidad en las zonas pobres y la segregación urbana, la cultura de la masculinidad y los cambios en el mercado local de la droga; (c) micro-sociales el incremento de las armas de fuego, el consumo de alcohol y las dificultades de expresión verbal de los sentimientos por las personas. El artículo concluye con un análisis sobre cómo la violencia está llevando no sólo a la pérdida de las ciudades, sino a la ciudadanía en América Latina.